Tunable Nanosensor With a Horizontal Number Eight-Shape Cavity in a MIM Waveguide System - Xu, Daijing; Yan, Shubin; Yang, Xiaoyu; Wang, Jinxi; Wu, Xiushan; Hua, Ertian (Frontiers in Physics, 2021)
Optical devices play an important role in different fields, such as refractive index detection in food processing and the biochemical industry. In our work, a novel nanoscale optical structure, composed of a metal-insulator-metal waveguide with a stub and a horizontal number eight-shape cavity (HNEC), is presented. The transmission properties of this structure are investigated in detail by using finite element method The effects of geometric parameters on sensing performance are studied in detail. Moreover, the influences of an asymmetric resonator caused by shifting central rectangular cavity of HNEC on transmission spectrum are discussed. The changing parameters of HNEC resonator have different effects on different resonance dips. Then, when the parameters of this presented structure are fixed as a of 540 nm, b of 340 nm, S of 0, l of 70 nm and g of 10 nm, this intriguing structure can serve as a refractive index sensor, whose maximum sensitivity can reach 1,500 nm/refractive index unit with a figure of merit of 75. Therefore, this structure will contribute to the development of miniaturization of optical devices.